Speed and sequencing of transition reforms and income inequality: A panel data analysis - David Aristei; Cristiano Perugini (Osteuropa-Institut Regensburg, 2011)
An extensive literature has analysed the economic effects of transition patterns in Central and Eastern European and former Soviet Union countries. With few recent exceptions, analysis of the impacts of speed and sequencing of reforms has not concerned the dynamics of income inequality. In this paper we analyse the heterogeneous effects of transition reforms on inequality by explicitly considering their speed and sequencing. To this aim we identify seven transition models in which the 27 countries considered can be classified. The dynamic panel econometric analysis for the period 1989-2006 reveals that balanced transition patterns, which favoured a coordination of reforms especially in specific fields, were relatively less pro-inequality.
Keywords: D31; C23; P21; P36; 330; Inequality; Transition; Reform speed and sequencing; Dynamic panel models; Systemtransformation; Übergangswirtschaft; Zeit; Einkommensverteilung; Verteilungswirkung; Panel; Schätzung; Osteuropa